EFEKTIVITAS PENGGUNAAN WHATSAPP GROUP TERHADAP PENINGKATAN PENGETAHUAN ORANG TUA AKAN KEGIATAN SEKOLAH (SURVEI PADA FOXES CLASS KIPINA KIDS KELAPA GADING 1) - Astrid Angelin Mayui; Silvina Mayasari; Sari Ekowati Hadi (CV Edujavare Publishing, 2025)
This study aims to examine the effectiveness of WhatsApp Group usage on parents’ knowledge regarding school activities in Foxes Class, at Kipina Kids Kelapa Gading 1. The background of this research highlights the importance of effective communication between schools and parents in early childhood education, particularly through digital media that are practical and easily accessible. The research method applied was quantitative with a questionnaire approach. The population consisted of 42 parents, with a sample of 38 respondents determined using Slovin’s formula with a 10% margin of error. The instrument used was a closed-ended Likert scale questionnaire distributed through Google Form in the class WhatsApp Group. Data were analyzed using validity and reliability tests, classical assumption tests, and simple linear regression analysis with the assistance of SPSS software. The result show that WhatsApp Group usage has a positive and significant influence on parental knowledge, as evidenced by a significance value of 0,001 < 0,05 and a t-value of 3,501 > ttabel of 2,028. The coefficient of determination indicated that 25,4% of the variation in parents' knowledge is explained by the use of WhatsApp Group, with the remaining percentage influenced by other factors. A Pearson correlation value 0.504 revealed a moderately strong and statistically significant relationship between the variables. These findings highlight the role of digital communication tools like WhatsApp in fostering effective collaboration between schools and families, particularly in early childhood education settings.